Pseudo cluster randomization - Borm, George (Henry Stewart Talks, 2007)
Individual randomization versus cluster randomization, Contamination as a possible problem with individual randomization, Possible problems with cluster randomization: selection bias and slow recruitment control arm, Pseudo cluster randomization as an alternative method: less contamination, less selection bias, better recruitment and statistically efficient, Formula to calculate power, Analysis methods
Archived at 2018/05/31